2015
DOI: 10.1093/nar/gkv1349
|View full text |Cite
|
Sign up to set email alerts
|

Assays for DNA double-strand break repair by microhomology-based end-joining repair mechanisms

Abstract: DNA double stranded breaks (DSBs) are one of the most deleterious types of DNA lesions. The main pathways responsible for repairing these breaks in eukaryotic cells are homologous recombination (HR) and non-homologous end-joining (NHEJ). However, a third group of still poorly characterized DSB repair pathways, collectively termed microhomology-mediated end-joining (MMEJ), relies on short homologies for the end-joining process. Here, we constructed GFP reporter assays to characterize and distinguish MMEJ varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
(42 reference statements)
3
27
0
Order By: Relevance
“…We have recently constructed a MMEJ‐specific GFP reporter assay, based on principles analogous to the HR and NHEJ reporter plasmids used above (Kostyrko and Mermod, ). Interestingly, the use of this reporter in CHO cells revealed that the majority of episomal DSBs were not re‐joined by a simple MMEJ pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently constructed a MMEJ‐specific GFP reporter assay, based on principles analogous to the HR and NHEJ reporter plasmids used above (Kostyrko and Mermod, ). Interestingly, the use of this reporter in CHO cells revealed that the majority of episomal DSBs were not re‐joined by a simple MMEJ pathway.…”
Section: Resultsmentioning
confidence: 99%
“…S3). Seventy percent of the analyzed repair products had no pre‐existing microhomology indicative of MMEJ, but they displayed direct or inverted repeat sequences associated SD‐MMEJ, up‐ or downstream of the repaired junction (Kostyrko and Mermod, ). We thus concluded that plasmid‐to‐plasmid joining relies mostly on a SD‐MMEJ pathway potentially involving DNA polymerase θ and Ligase III, and that the simple MMEJ mechanism is seldom used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alt‐EJ has been described to be a back‐up repair system when other DNA repair pathways are compromised (Wang et al ., ; McVey & Lee, ), but its role could be more pre‐eminent than previously reported (Sfeir & Symington, ; Wang & Xu, ). Different publications have identified POLQ as one of the main enzymes involved in the Alt‐EJ‐mediated DNA repair (Chan et al ., ; Kent et al ., ; Kostyrko & Mermod, ) but its role is still not fully understood. In this study, we analysed the role of the P. patens POLQ protein in DNA repair.…”
Section: Discussionmentioning
confidence: 99%